Role of non-invasive imaging in perioperative neurocognitive disorders - Vandiver, M. Scott (Frontiers in Anesthesiology, 2023)
Perioperative Neurocognitive disorders, including delirium and long-term cognitive dysfunction following surgery, are an ever-increasing focus of investigation for anesthesiologists and researchers. The desire to bring patients safely through the perioperative period with an absolute minimum impact of the anesthetic, surgery, and post-operative period on the patient's functional status has brought a high level of scrutiny to entities that most impact patients. Perioperative neurocognitive disorders (PND) have the potential to vastly alter patient functional status after surgery and anesthesiologists are often the first physician asked about the effects this may have on the patient during the informed consent process. While the underlying mechanisms of PND are not well understood, more tools are being brought to bear with non-invasive imaging shedding light on the pathophysiology of PND. In this narrative mini-review, we discuss the current investigation into PND with a focus on non-invasive imaging and preventative strategies that are being employed to better protect patients.